Perkembangan Usaha Agribisnis Bunga Anggrek Vanda Potong pada Kembang Batur Anggrek Collection di Desa Sanur Kaja Denpasar - LIZA PRISKA NOVI YANTI; I KETUT SUAMBA; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
The Business Growth of Cut Orchid Vanda Flower in Kembang Batur AnggrekCollection at Desa Sanur Kaja Denpasar Timur, Denpasar-Bali Increasing number of flowrist at Denpasar City make every company must havemore value to attract consumers. Kembang Batur Anggrek Collection is one of theflowrist that supply consumer’s need at Denpasar. The purpose of the study todetermine how the business growth of cut orchid Vanda flower observed form profit,volume of sales, and constraints in Kembang Batur Anggrek Collection. The resultsof this study shows profit growth in the TR calculation is Rp 5.831.500.000,00 ; theTC calculation is Rp 3.704.811.000,00 and the calculation profit obtained is Rp2.126.689.000 over ten years. The average business profits of cut orchid Vandaflower in Kembang Batur Anggrek Collection is Rp 212.668.900,00 every year andthe sales volume of the annual accounts showed an increasing sales. The cultivationof Cut Orchid Vanda Flower in Kembang Batur Anggrek Collection should becontinued and developed with effort leads to an increase in the number ofproduction. In order to fulfill the increasing market demand of Cut Orchid VandaFlower.